Jon Fosse i Polen - en utakknemlig begynnelse - Grossman-Kliber, Monika (Folia Scandinavica Posnaniensia, 2007)
The article concentrates on the reception of Jon Fosse’s plays in Poland, where the dramatist remains practically unknown, although he has recently become the most frequently staged playwright in Europe. It seems that Fosses dramas have not found understanding among Polish critics. The article analyses the reviews of Fosse’s dramas published in Polish press until May 2004. Till then only three plays were staged in Polish theatres and five were translated. The author points out that Fosse’s dramas in Poland, rather than being a permanent element of the repertoire, are frequently staged as parts of various theatrical projects aiming at finding new solutions for modern drama and theatre. Finally, she concludes that the dialogue of Fosse’s plays is always their most original (although often controversial) element, regardless of the language of translation.